Spatial Analysis of International Tourist Movement to Langkawi for 2010 and 2011 - Nur Fatma Zuhra, Basiron; Azizul, Ahmad; Tarmiji, Masron (2014)
Tourism is a temporary movement of people to a destination of their choice intended for leisure or recreation. The resulting of this movement can be divided into interdestination dan intradestinastion. This study is about interdestination movement which is characterised by movement from tourist-generating regions to one or more destinations. This research aims to analyse the movement of international tourist who come to Langkawi in 2010 and 2011. The application geographic information system (GIS) is aids in visualizing spatial data through mapping. Regression analysis using SPSS was also used to examine the relationship between the distance and the amount of flow that exists. Map of the distribution and flow of tourist was produced to facilitate the analysis. The results of the analyses show that the tourist movement is driven by certain factors such as climatic, economic, distance and etc. Regression analysis showed the nexus between the distance and the amount of the tourist flow was not strong. Map produced can be used by LADA specifically for planning marketing strategies and etc.